The Effect of Chia Seeds (Salvia hispanica L.) Consumption on Health A Literature Review - Skowron, Aleksandra; Orzeł, Jakub; Pelczar, Patrycja; Przygoda, Aleksandra (Quality in Sport, 2026)
Background. Chia (Salvia hispanica) is a plant species native to Mexico and Guatemala. Chia seeds possess significant nutritional properties, as they contain a high amount of antioxidants, as well as minerals valuable for human health and vitamins E, B1, and B3. Chia seed oil contains a very high concentration of omega-3 fatty acids. Due to their high nutritional value, chia seeds are recommended for inclusion in the daily diet of both adults and children. Methodology. A review was conducted using PubMed. Search terms included: chia seeds, salvia hispanica, omega-3 acids, alpha-linolenic acid. Studies published between 2019 and 2025 were reviewed. Results. Chia seeds (Salvia hispanica) are highly nutritious, due to their high dietary fiber content (approx. 30–35%), which has a beneficial effect on intestinal motility and glucose metabolism. They are a rich source of α-linolenic acid (ALA) from the omega-3 group, which exhibits cardioprotective effects, positively influences the lipid profile, and reduces the risk of cardiovascular diseases, as well as being a very important component of neuronal membranes, crucial for the development of the nervous system. Chia seeds also provide significant amounts of minerals, particularly calcium, magnesium, phosphorus, and iron, which may support the functioning of the skeletal and enzymatic systems. The presence of phenolic compounds and other antioxidants contributes to the reduction of oxidative stress and may have anti-inflammatory effects. Conclusions. Salvia hispanica offers broad therapeutic potential in nutrition and preventive potential in medicine in particular in children, for whom an adequate intake of omega-3 fatty acids is crucial due to the rapid development of their nervous system, as well as the development of the heart and circulatory system. Chia has cardioprotective, neuroprotective, and anti-inflammatory properties and has a positive effect on intestinal function.